High performance Mg2+/Li+ separation membranes modified by a bis-quaternary ammonium salt - Xu, Yang; Peng, Huawen; Luo, Hao; Zhang, Qi; Liu, Zhitian; Zhao, Qiang (Desalination, 2022)
The separation of lithium (Li+, 3.8 Å) and magnesium (Mg2+, 4.3 Å) ions represents the main challenge for lithium extraction from salt lakes with high magnesium-to‑lithium (Mg2+/Li+) ratio. A bis-quaternary ammonium salt (abbreviated as QEDTP) was designed to modify Polyethyleneimine (PEI) polyamide nanofiltration membrane. Water flux of the modified PEI membrane is 126.9 ± 1.6 L·m−2·h−1 (LMH) under 6 bar hydraulic pressure, which is 4.4 times as high as the pristine PEI membrane (25.8 ± 0.3 LMH). Meanwhile, the MgCl2 rejections of both membranes are maintained >95%. Nanofiltration performance of the QEDTP membrane is stable in 180 h continuous nanofiltration test at 6 bar pressure. The water flux and Mg2+/Li+ selectivity (SMg2+/Li+) of the QEDTP modified membrane in filtrating 2000 ppm Mg2+/Li+ mixture (Mg2+/Li+ ratio: 120:1, 6 bar) are 112.9 ± 1.6 LMH and 15.6 ± 0.3, which is one of the best Mg2+/Li+ separation performance considering both the flux and selectivity. A bis-quaternary ammonium salt was grafted to surfaces of a PEI nanofiltration membrane, resulting in ~4 times improved water flux combined with good Mg2+/Li+ separation performance. [Display omitted] •PEI nanofiltration membranes were modified with a bis-quaternary ammonium salt•Water permeance of the modified membrane was ~4 times as high as the pristine membrane•The modified membrane exhibits high permeance, Mg2+/Li+ selectivity, and stability